Strong asymptotics of extremal polynomials on the segment in the presence of denumerable set of mass points - Khaldi, Rabah; Boucenna, Ahcene (Rev. Anal. Numér. Théor. Approx., 2011)
The strong asymptotics of the monic extremal polynomials with respect to a \(L_{p}(σ )\) norm are studied. The measure \(σ \) is concentrated on the segment \([-1,1]\) plus a denumerable set of mass points which accumulate at the boundary points of \([-1,1]\) only. Under the assumptions that the mass points satisfy Blaschke's condition and that the absolutely continuous part of \(σ \) satisfies Szeg?'s condition.